Images of Immigrants and Refugees in Western Europe - d'Haenens, Leen; Joris, Willem; Heinderyckx, François (Leuven University Press, 2019)
"The topic of migration has become particularly contentious in national and international debates. Media have a discernable impact on overall societal attitudes towards this phenomenon. Polls show time and again that immigration is one of the most important issues occupying people's minds. This book examines the dynamic interplay between media representations of migrants and refugees on the one hand and the governmental and societal (re)actions to these on the other. Largely focusing on Belgium and Sweden, this collection of interdisciplinary research essays attempts to unravel the determinants of people's preferences regarding migration policy, expectations towards newcomers, and economic, humanitarian and cultural concerns about immigration's effect on the majority population's life. Whilst migrants and refugees remain voiceless and highly underrepresented in the legacy media, this volume allows their voices to be heard. Contributors: Leen d'Haenens (KU Leuven), Willem Joris (KU Leuven), Paul Puschmann (KU Leuven/Radboud University Nijmegen), Ebba Sundin (Halmstad University), David De Coninck (KU Leuven), Rozane De Cock (KU Leuven), Valériane Mistiaen (Université libre de Bruxelles), Lutgard Lams (KU Leuven), Stefan Mertens (KU Leuven), Olivier Standaert (UC Louvain), Hanne Vandenberghe (KU Leuven), Koen Matthijs (KU Leuven), Kevin Smets (Vrije Universiteit Brussel), Jacinthe Mazzocchetti (UC Louvain), Lorraine Gerstmans (UC Louvain), Lien Mostmans (Vrije Universiteit Brussel), and François Heinderyckx (Université libre de Bruxelles)"